2010
DOI: 10.1007/978-3-211-99370-5_18
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Laser Discectomy: Experience and Long Term Follow-Up

Abstract: The classical microsurgical approach in the treatment of herniated nucleus pulposus (HNP) has been substituted over the years by endoscopical approach, in which it is possible to practice via endoscopy a laser thermo-discoplasty, and by percutaneous laser disc decompression and nucleotomy. Percutaneous laser disc decompression and nucleotomy have been performed worldwide in more than 40,000 cases of HNP. Because water is the major component of the intervertebral disc and in HNP pain is caused by disc protrusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 9 publications
0
16
0
3
Order By: Relevance
“…After the solid‐state lasers, gas lasers were developed 24–28. In the last decade, the diode laser 29–31, which currently dominates in surgical use, was introduced. Its size and the ability to set the wavelength, output powers, and delivery through quartz fibers make it applicable to many different procedures.…”
Section: Introductionmentioning
confidence: 99%
“…After the solid‐state lasers, gas lasers were developed 24–28. In the last decade, the diode laser 29–31, which currently dominates in surgical use, was introduced. Its size and the ability to set the wavelength, output powers, and delivery through quartz fibers make it applicable to many different procedures.…”
Section: Introductionmentioning
confidence: 99%
“…These authors concluded that the 980-nm diode laser had excellent ablation capacity with minimal thermal side effects on nearby tissues. 1 Although application of the 980-nm diode laser in the neurosurgical field has been demonstrated in intracranial neoplasms and lumbar discogenic pain, 2,8,9 we demonstrate its use with endoscopy for the first time. Our intention is to reduce the invasiveness of intracranial procedures while preventing brain tissue trauma, to decrease the risk of neurological and mental deficits.…”
Section: 418mentioning
confidence: 81%
“…Then, laser technology was developed and Ion Resonance Laser, Excimer Laser and Argon Laser types were developed. In a retrospective study performed by Menchetti et al , they applied PLDD in selected patients and they reported that there was a 70% success rate in the 5 years follow-up period and there was no complication 11 . Gronemeyer had 74% successful results in the 4 years follow-up period of 200 patients 12 .…”
Section: Discussionmentioning
confidence: 99%